The Implementation Of GMP, SSOP, and HACCP in the Processing of Frozen Yellowfin Tuna (Thunnus Albacares) at UD Damena. - Prinata, Made Ryan; Darmadi, Ni Made; Kawan, I Made (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of the study was to identify and analyze the implementation of GMP, SSOP, and HACCP. The method used in this research was a descriptive research method, to understand the implementation of GMP, SSOP, HACCP in the handling of frozen yellowfin tuna (Thunnus albacares) at UD Damena. Data collection techniques used in the research were observation, interviews, participation, and documentation. Based on the research results, it was found that UD Damena had met the basic requirements in the form of GMP and SSOP in accordance with Minister of Marine Affairs and Fisheries Regulation Number 17 of 2019. UD Damena also implemented the five steps and seven principles of HACCP well in accordance with SNI 01-4852-1998 as a form of consumer protection in consuming fishery products, so that export activities ran effectively and efficiently without any cases of product rejection in the destination countries. The implementation of GMP and SSOP systems at UD Damena had been carried out well and optimally. The implementation of HACCP in UD Damena had been applied well, by coordinating with the HACCP team.